The Effect of Using Educaplay Media on English Learning Outcomes of Grade 5th Elementary School Students - Sutra Dewi; Abdul Rahman; Rahmawati Patta (Universitas Islam Negeri Palopo, 2025)
This study aims to determine 1) the effect of using Educaplay media on the English learning outcomes (specifically vocabulary mastery) of fifth-grade students at SDN 24 Pakkanna in Wajo Regency, and 2) the perceptions of fifth-grade students at SDN 24 Pakkanna regarding the use of Educaplay media in English learning. The type of research used is a quasi-experimental design using the Nonequivalent Posttest Only Control Group Design. The population and sample in this study consisted of 40 fifth-grade students, with class V B (20 students) as the experimental class and class V A (20 students) as the control class selected through purposive sampling. The intervention in the experimental class was carried out over three treatment sessions. The data collection techniques used tests, questionnaires, and documentation with descriptive and inferential data analysis. The results of the descriptive analysis of the questionnaire showed that students' perceptions of the use of Educaplay media in English learning were in the very good (85%) and good (15%) categories. Based on the results of inferential statistical analysis, p < 0.001 is smaller than α = 0.05 using an independent sample t-test, which shows that H₀ is rejected and Ha is accepted, indicating that there is a significant difference in learning outcomes between the class receiving treatment using Educaplay media and the class not receiving the same treatment. Based on the research results, it can be concluded that there is an effect of using Educaplay media on the English learning outcomes of fifth-grade students at SDN 24 Pakkanna, as well as very good perceptions from the majority of students.